The Effect of Integrating Pragmatic Features of Conversational Implicatures in Grammar Teaching on Indonesian University EFL Learners - Adam, Sutisno; Sailuddin, Sartika Putri (Universitas Pendidikan Mandalika, 2025)
One of the challenges that language teachers face is developing the language competence of Foreign Language learners so that they can use language correctly and appropriately in a variety of social contexts. This study aims to observe whether there is an effect of pragmatic instruction in EFL classroom to learners’ grammatical and pragmatic competence. The data collected were from year 2 English students by using grammatical and pragmatic pre-tests and post-test for students to answer. Students were divided into two groups of the treatment group which receive pragmatic instructions of implied meanings and the control group which received regular teaching. Students’ answers in the tests were analysed quantitatively to obtain the mean score and further will be compared. The results show that: 1) students perform low on both aspects in both pretest and posttest (m1.1=3.63, m1.2=4.83, m2.1=4.27, and m2.2=3.47), 2) there is a moderate positive effect of pragmatic instruction on students’ grammatical competence (t(60)=-3.73, p=0.000), and 3) there’s no effect of pragmatic instruction on students’ pragmatic competence (t(65)=1.73, p=0.089). This finding indicates the role that explicit pragmatic instruction may play in boosting EFL learners’ grammatical development, along with the extensive grammar learning that learners received. It suggests the need EFL curricula revision through incorporating pragmatic features in grammatical subjects. In this way, grammar learning can be improved, and pragmatic teaching model can also be created.